Influence of a biofilm bioreactor on water quality and microbial communities in a hypereutrophic urban river. Issue 9 (16th April 2021) - Cai, Xianlei; Yao, Ling; Sheng, Qiyue; Jiang, Luyao; Wang, Ting; Dahlgren, Randy A.; Deng, Huanhuan
ABSTRACT: Biofilms play an important role in degradation, transformation and assimilation of anthropogenic pollutants in aquatic ecosystems. In this study, we assembled a tubular bioreactor containing a biofilm substrate and aeration device, which was introduced into mesocosms to explore the effects of bioreactor on physicochemical and microbial characteristics of a hypereutrophic urban river. The biofilm bioreactor greatly improved water quality, especially by decreasing dissolved inorganic nitrogen (DIN) concentrations, suggesting that biofilms were the major sites of nitrification and denitrification with an oxygen concentration gradient. The biofilm bioreactor increased the abundance of planktonic bacteria, whereas diversity of the planktonic microbial community decreased. Sequencing revealed that Proteobacteria, Bacteroidetes, Planctomycetes, and Actinobacteria were the four predominant phyla in the planktonic microbial community, and the presence of the biofilm bioreactor increased the relative abundance of Proteobacteria. Variations in microbial communities were most strongly affected by the presence of the biofilm bioreactor, as indicated by principal component analysis (PCA) and redundancy analysis (RDA). This study provides valuable insights into changes in ecological characteristics associated with self-purification processes in hypereutrophic urban rivers, and may be of important for the application of biofilm bioreactor in natural urban river. GRAPHICAL ABSTRACT: